Accuracy of Qibla Direction Mosque at Rest Area Toll Road on the Qibla Jurisprudence Perspective - Kusdiyana; Samsudin; Muhammad Wildan Nur Akmal (NUSANTARA: Journal Of Law Studies, 2023)
This research normatively analyzes the accuracy of the Qibla direction of mosques in public places such as the rest area on Cipali Toll Road. This research approach is qualitative. The results of testing the accuracy of the Qibla direction show that there is a difference between the Qibla direction of the mosque and the Qibla direction calculated by the researcher. The smallest value is 1 degree and the largest value is 28 degrees. The factors causing the inaccuracy of the Qibla direction of the Cipali toll rest area mosque are: 1) Not going through a calculation process, 2) only using a mobile application, 3) and the presence of human error when excavating the foundation of the mosque building. Meanwhile, from the perspective of jurisprudence, there is only one mosque that is still almost included in the scope of al-Ka'bah jihad, namely the al-Firdaus mosque. Penelitian ini  menganalisis secara normatif ketepatan arah kiblat masjid di tempat umum seperti rest area di Jalan Tol Cipali. Pendekatan penelitian ini adalah kualitatif. Hasil pengujian akurasi arah kiblat menunjukkan adanya perbedaan antara arah kiblat masjid dengan arah kiblat yang dihitung oleh peneliti. Nilai terkecil 1 derajat dan nilai terbesar 28 derajat. Adapun faktor penyebab ketidaktepatan arah kiblat masjid rest area tol Cipali adalah: 1) Tidak melalui proses perhitungan, 2) hanya menggunakan aplikasi mobile, 3) dan adanya human error saat penggalian pondasi masjid bangunan. Sedangkan dari segi fikih, hanya ada satu masjid yang masih hampir masuk dalam ruang lingkup jihad al-Ka’bah, yaitu masjid al-Firdaus.